Karakteristik Geomorfologi dan Proses Pembentukannya di Daerah Tilangobula, Kabupaten Bone Bolango - Slamet Slamet; Yayu Indriati Arifin; Muh Kasim; Alifia Widya Warapsari Badaru (Universitas Negeri Gorontalo, 2025)
This study examines the geomorphological characteristics of Tilangobula Village in East Suwawa District, Bone Bolango Regency, Gorontalo Province, Indonesia, located within the tectonically active Limboto Zone. Through integrated field observations and geospatial analysis—including topographic maps, slope gradients, and drainage patterns—the research identifies structural hills as the dominant geomorphological unit, covering 2.356 km² with elevations ranging from 200 to 600 meters above sea level. The area exhibits two distinct drainage patterns (parallel and trellis) and variable slope gradients (2–140%). Morphogenetic analysis reveals the landscape has been shaped by both endogenic processes (notably oblique faulting, specifically a Normal Left Slip Fault) and exogenic factors (erosion of diorite and quartz diorite intrusions). The lithology comprises intrusive igneous rocks (diorite and quartz diorite), with structural features such as shear joints and faults further influencing the terrain. The findings highlight the interplay between tectonic forces and surface processes in forming the region’s unique structural hills, characterized by V-shaped valleys and steep slopes. This study provides critical baseline data for understanding understudied tectonic landscapes in eastern Indonesia and supports applications in regional geological research and land-use planning. The results underscore the importance of integrating morphographic, morphometric, and morphogenetic analyses to decipher complex geomorphological evolution in tectonically active regions.